ANALISIS YURIDIS TERHADAP KESEPAKATAN DALAM TRANSAKSI ELEKTRONIK: JURIDIC ANALYSIS OF DEALS IN ELECTRONIC TRANSACTIONS - Ade Putra F Sumbara; Tira, Andi; Almusawir (Faculty Of Law Bosowa University, 2021)
This study aims to determine the occurrence of agreements in electronic transactions, and forms of dispute resolution in electronic transactions. Thisaresearch was conducted in Makassar Cityausing normative legal research methods, namely research that uses data collection as the main data source and/or data collection through interviews as the main resource person. The results show that there is an agreement in an electronic transaction if there is an offer, acceptance, payment, and delivery, this has been regulated in Government Regulation number 80 of 2019 concerning trading through electronic systems, there are two forms of dispute resolution in electronic transactions, namely legal remedies Preventive measures can be interpreted as all efforts made to prevent the occurrence of an unwanted event or situation. In e-commerce transactions, this unwanted situation is the occurrence of losses, especially losses on the part of consumers and secondly, repressive legal remedies are legal remedies taken to resolve a legal problem that has already occurred. This legal remedy is used if there has been a dispute between business actors and consumers.